Does the Stenting Versus Aggressive Medical Therapy Trial Support Stenting for Subgroups With Intracranial Stenosis?. Issue 11 (November 2015) - Lutsep, Helmi L.; Lynn, Michael J.; Cotsonis, George A.; Derdeyn, Colin P.; Turan, Tanya N.; Fiorella, David; Janis, L. Scott; Lane, Bethany F.; Montgomery, Jean; Chimowitz, Marc I.
Abstract : Background and Purpose—: Although the Stenting Versus Aggressive Medical Therapy for Intracranial Arterial Stenosis (SAMMPRIS) trial showed that medical therapy alone was superior to stenting plus medical therapy for preventing recurrent strokes in patients with symptomatic intracranial stenosis, we determined whether SAMMPRIS supported the use of stenting in any subpopulations of patients with symptomatic intracranial arterial stenosis. Methods—: The primary outcome, 30-day stroke and death and later strokes in the territory of the qualifying artery, was compared in those with and without baseline factors in the 2 treatment arms, percutaneous transluminal angioplasty and stenting (PTAS) plus aggressive medical therapy versus aggressive medical therapy alone. Baseline factors included sex, age, race, diabetes mellitus, hypertension, lipid disorder, smoking status, type of qualifying event, qualifying event hypoperfusion symptoms, use of antithrombotic or proton pump inhibitor at baseline, days to enrollment, old infarcts in the same territory, percent stenosis, other artery stenosis, and location of the symptomatic artery. Results—: A total of 451 patients were enrolled, 227 randomized to aggressive medical therapy and 224 to PTAS. Of all variables evaluated, the observed 2-year event rates were higher with PTAS than with aggressive medical therapy in the vast majority and the interaction with treatment was not statistically significant for any of the factors. Conclusions—: The SAMMPRIS results do not provide evidence to support the use of PTAS using the Wingspan stent system compared with medical treatment in any examined subpopulation of patients with symptomatic intracranial stenosis, including those with qualifying event hypoperfusion symptoms. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00576693.